Detecting fetal subchromosomal aberrations by MPS: an unexpected discrepancy between amniocyte DNA and ccffDNA. (6th February 2014) - Buysse, Karen; de, Joep; Janssen, Irene M.; van, Bregje W. M.; Gomes, Ingrid; Hehir‐Kwa, Jayne; Eggink, Alex J.; van, John M. G.; Vissers, Lisenka E. L. M.; Geurts van Kessel, Ad; Faas, Brigitte H. W.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Noninvasive prenatal detection of fetal aneuploidies by massively parallel sequencing of circulating cell‐free fetal DNA has recently become widely available. Few studies report the detection of submicroscopic chromosomal aberrations. What does this study add? A ~400 kb gain and a ~27 Mb loss were detected on chromosome 13q by genomic microarray analysis of amniocyte DNA. Testing circulating cell‐free fetal DNA not only revealed the same loss but also a much larger gain (~12 Mb), indicating discrepancies between DNA of true fetal and placental origin. The use of a windowed approach is recommended in case of unexpected 'whole chromosome' noninvasive prenatal testing results and/or when fetal anomalies are suggestive for subchromosomal aberrations.